Arboretum as Carbon Stock and Carbon dioxide Uptake to Support the Realization of Green Campus at Riau University - Sri Wulandari (Talenta Publisher, 2020)
The University of Riau Arboretum is one of the natural environments contained within the campus, having various types of vegetation that can be utilized to support the realization of a green campus. This study aims to determine the benefits of arboretum as carbon reserves and CO2 uptake to support the realization of Riau University's green campus. Research using survey methods by observing in the arboretum. Determination of sampling locations by purposive random sampling by considering the condition of vegetation and topography. Research parameters are: (1) vegetation analysis; (2) carbon stocks and (3) CO2 uptake. The University of Riau Arboretum has a vegetation composition in all strata, namely seedlings, saplings, poles and trees. The number of individual seedlings is higher than other strata, namely 349 individuals. Diversity index in all strata classified as high criteria ranged from 3.22 to 3.42. The total carbon stock of 1.12 tons / ha and CO2 absorption of 4.11 tons / ha, with the arboretum of Riau University (± 10 ha), the CO2 absorption that occurs is 41.1 tons. Thus the existence of arboretum can be used to further optimize its function as carbon reserves and CO2 absorption in realizing the green campus program of the University of Riau.Arboretum